The Hidden Prince - Afshar, Tessa (Thorndike, Maine : Center Point Large Print, 2023)
"The beloved daughter of Jewish captives in Babylon, Keren is sold into Daniels household to help her family survive. She becomes Daniels most trusted scribe, while taking lessons and swordsmanship training alongside Daniels sons and their best friend, Jared. But after a tragic accident changes the course of her life, Keren finds herself in a foreign country, charged with a mysterious task: teaching a shepherd boy how to become a lord. When she overhears whispers that hint at his true identity, she realizes she must protect him from the schemes of a bloodthirsty king. Jared cannot forgive Keren. Still, he finds himself traveling over mountains to fetch her back to the safety of home. When he discovers the secret identity of Kerens pupil, Jared knows he must help protect him. Love battles bitterness as they flee from the kings agents, trying to save the boy who could one day deliver their people from captivity."--
Keywords: Scribes, Jewish -- Fiction; Man-woman relationships -- Fiction; Women slaves (Jewish law) -- Fiction; Princes -- Fiction; Survival -- Fiction; Babylon (Extinct city) -- Fiction; Christian fiction; Bible fiction; Historical fiction; Large print books